Military Based Security System Using Raspberry Pi (International Journal of Engineering and Computer Science, 2018)
In today’s world Indian border military force is facing a huge destruction. Hence, most of the military organizations         take the help of military robots to carry out risky jobs which cannot be handled by humans. In this proposal, we design and implement in such a way that the robotic vehicle can enter into an area of higher risks, move and place wherever the object wants to go and captures intruder’s image. It has human detection Pi camera and temperature and gas detecting sensor that can provide precaution to potential crimes, fire and leakage of any gases. The credit card sized Raspberry Pi with Open Source Computer Vision (OpenCV) software controls the face detection algorithm and sends captured pictures to the user’s email via WI-FI. The pi-camera serves as the eye of the robot and provides us live video streaming. The biggest advantage of the system is that the user can get the picture of the intruder from anywhere in the world and can respond according to the risks in the situations.       The prime objectives of this paper are:• To find the presence of an intruder - if detects, captures images and sends it to the given email address.• Enables control of the robotic vehicle –i.e. The robot can be moved in any directions from the user present in any location.• To find the presence of any gases present in the surrounding other than the normal air and warns the nearby person with its buzzing.• Can monitor the location at any remote distance via live surveillance.• To find the temperature of the environment